2020
DOI: 10.1177/0300060520966538
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gonadotropins and endometrial thickness on pregnancy outcome in patients with unexplained infertility or polycystic ovarian syndrome undergoing intrauterine insemination

Abstract: Objective The purpose of this study was to investigate the effect of gonadotropin dose and endometrial thickness (EMT) on pregnancy outcome in patients undergoing intrauterine insemination (IUI). Methods We retrospectively analyzed data from 361 patients with unexplained infertility or polycystic ovarian syndrome (PCOS) who underwent 930 IUI cycles treated with gonadotropins. Then, we measured the effects of gonadotropins and EMT on the clinical pregnancy rate. Finally, we assessed the association of various d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…In the current study, there was no significant difference in mean endometrial thickness between the L-carnitine group and placebo groups; this indicates that treatment with L-carnitine has no significant impact on endometrial thickness in women with PCOS. It has been documented that endometrial thickness can significantly affect pregnancy outcomes in women with PCOS, 10,11 but, the insignificant variation in endometrial thickness between the L-carnitine group and placebo group will raise the possibility of another determinant of successful pregnancy outcome in women with PCOS treated with L-carnitine. Ismail et al 12 in 2014 had stated that L-carnitine treatment significantly improved endometrial thickness in PCOS women; however, it disagrees with Ismail et al in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, there was no significant difference in mean endometrial thickness between the L-carnitine group and placebo groups; this indicates that treatment with L-carnitine has no significant impact on endometrial thickness in women with PCOS. It has been documented that endometrial thickness can significantly affect pregnancy outcomes in women with PCOS, 10,11 but, the insignificant variation in endometrial thickness between the L-carnitine group and placebo group will raise the possibility of another determinant of successful pregnancy outcome in women with PCOS treated with L-carnitine. Ismail et al 12 in 2014 had stated that L-carnitine treatment significantly improved endometrial thickness in PCOS women; however, it disagrees with Ismail et al in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…16,[30][31][32] Li et al found that the increase of endometrial thickness can significantly improve the clinical pregnancy rate after IUI. 33 In addition, study has shown that endometrial thickness has no predictive value for IUI outcomes. 34 Wolff EF et al showed that the pregnancy rate after IUI was significantly increased with the increasing endometrial thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in women with very thin uterine linings on oral medications or for those patients who failed to respond to oral medications with ovulation. [ 4 , 5 ]. In a large study of 50,473 stimulated IUI cycles performed in women less than 40 years of age, a cut-off of two mature follicles was found to limit the risk of twin pregnancy, obtained good conception outcomes, and minimized the risk of higher-order multiple pregnancies [ 6 ].…”
Section: Introductionmentioning
confidence: 99%